1999
DOI: 10.1007/s002200050620
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Theorem without a Gap Condition

Abstract: We prove an adiabatic theorem for the ground state of the Dicke model in a slowly rotating magnetic field and show that for weak electron-photon coupling, the adiabatic time scale is close to the time scale of the corresponding two level system-without the quantized radiation field. There is a correction to this time scale which is the Lamb shift of the model. The photon field affect the rate of approach to the adiabatic limit through a logarithmic correction originating from an infrared singularity characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
244
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(257 citation statements)
references
References 42 publications
5
244
0
8
Order By: Relevance
“…The relevant gap is now the gap between the discs. In this way, we showed that the relevant gap to consider is the gap between eigenmanifolds and not simply between the ground state and an excited state [2,11,12]. This is so, since these types of problems have large degeneracies in the ground state of H P , and the standard adiabatic theorem of quantum mechanics is not designed to handle these cases.…”
Section: Discussionmentioning
confidence: 98%
“…The relevant gap is now the gap between the discs. In this way, we showed that the relevant gap to consider is the gap between eigenmanifolds and not simply between the ground state and an excited state [2,11,12]. This is so, since these types of problems have large degeneracies in the ground state of H P , and the standard adiabatic theorem of quantum mechanics is not designed to handle these cases.…”
Section: Discussionmentioning
confidence: 98%
“…32 For this to be true, the changes must occur on a time scale that is long compared to the characteristic time associated with the gap separating the eigenvalue of interest from the rest of the energy spectrum. Recently, Avron and Elgart have formulated an extension of the QAT to cover systems with no spectral gaps, 33 which is the case presented by the quasibound states described here. As these authors have shown, all one really needs for adiabatic evoultion is a finite-dimensional spectral projection for the Hamiltonian that depends smoothly on time.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…As noted in Ref. 33, such queries require painstaking analysis to elucidate the optimal criteria for each particular case, a task we leave to future study.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Although outside the context of scattering theory, adiabatic switching and the Gell-Mann-Low formula have been subject of active research recently; see, e.g., [12][13][14][15][16][17][18] and references therein.…”
Section: Adiabatic Switchingmentioning
confidence: 99%